Using the theory of planned behaviour (TPB) in predicting the intent to use the internet for academic purposes - Bidin, Zainol; Md Hashim, Mohd Farid Asraf; Zakiyah, Sharif; Mohd Shamsudin, Faridahwati (Universiti Utara Malaysia, 2011)
Purpose – This study sought to investigate the factors that influence students’ intention to use the Internet for academic purposes in Universiti Utara Malaysia. This study applies theory of planned behaviour (TPB) as the base model. The model employed the original variables from the theory i.e. attitudes, subjective norms, perceived behavioural control and intention.Method – A survey involving of questionnaires was conducted among 369 public university students. Multiple regression was employed to examine the factors influencing intention to use the Internet for academic purposes.Findings – Results revealed that the variables attitude, subjective norms, and perceived behavioural control are statistically significant in influencing intention to use the Internet for learning purposes.It was also found that 38% of the variance in students’ intention to use the Internet is cumulatively explained by their attitude, subjective norms, and perceived behavioural control.Significance – The paper provides useful scientific insight into the relationships between attitude, subjective norms and perceived behavioural control variables towards intention to use the Internet for academic purposes. The ﬁndings can be used to promote the use of Internet among students in enhancing their learning experience.